2022
DOI: 10.1186/s10020-022-00511-7
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl diphosphate synthase regulated endothelial proliferation and autophagy during rat pulmonary arterial hypertension induced by monocrotaline

Abstract: Background The proliferation ability and autophagy level of pulmonary artery endothelial cells (PAECs) play an important role in promoting the development of pulmonary artery hypertension (PAH), and there is still no effective treatment for PAH. Farnesyl diphosphate synthase (FDPS) is a key enzyme in the mevalonate pathway. The intermediate metabolites of this pathway are closely related to the activity of autophagy-associated small G proteins, including Ras-related C3 botulinum toxin substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Rac1 was choose for further experiments due to RAC1 activation leads to increased proliferation of PASMCs and contributes to the development of pulmonary vascular remodeling (Fig. 5 B) (Zheng et al 2023 ; Jin et al 2022 ; Dilasser et al 2022 ). The reports results of dual luciferase showed that compared to the Exo-Ve, the luciferase activity of Rac1-WT showed significant inhibition of by Exo-ITGB1, while no difference was observed in the Rac1-MUT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rac1 was choose for further experiments due to RAC1 activation leads to increased proliferation of PASMCs and contributes to the development of pulmonary vascular remodeling (Fig. 5 B) (Zheng et al 2023 ; Jin et al 2022 ; Dilasser et al 2022 ). The reports results of dual luciferase showed that compared to the Exo-Ve, the luciferase activity of Rac1-WT showed significant inhibition of by Exo-ITGB1, while no difference was observed in the Rac1-MUT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some scholars have reported that DPP4 knockout promotes proliferation and activation of CREB/ aromatase pathway in GCs, thereby alleviating PCOS [39]. Recent accumulated evidence revealed that FDPS has been found to be involved in various biological functions and disease processes, such as FDPS regulates endothelial cell proliferation and autophagy [13]. In consistent with the above results, our research proved FDPS was closely related to the proliferation of GCs that knockdown of FDPS inhibited proliferation of GCs, while overexpression of FDPS promoted proliferation of GCs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, FDPS regulate cell growth and survival through GTPase/AKT axis, ERK, and STAT3 [12]. Some studies have found that inhibiting FDPS can reduce the activation of Rac1, which is closely associated with the PI3K/AKT/mTOR pathway [13].In addition, it also has a regulatory role in a variety of diseases, including malignancies (e.g., prostate cancer, glioblastoma) [12,14], cardiac dysfunction [15], pulmonary artery hypertension [13], and diabetes [16]. However, the role of FDPS in PCOS patients is unclear and more research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al. demonstrated that farnesyl diphosphate synthase (FDPS) contributes to active small G protein-induced autophagy during PAH ( 35 ). In a separate investigation, it was found that glucagon-like peptide-1 (GLP-1) receptor agonist, liraglutide, can suppress the proliferation of PASMCs by inhibiting cellular Drp1/nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) pathways and Atg-5/Atg-7/Beclin-1/LC3β-dependent pathways of autophagy in PAH ( 36 ).…”
Section: Programmed Cell Death In Pahmentioning
confidence: 99%